Developing a Solution for Nasal and Olfactory Transport of Nanomaterials. (April 2022) - O'Connell, Ryan C.; Dodd, Tiana M.; Clingerman, Sidney M.; Fluharty, Kara L.; Coyle, Jayme; Stueckle, Todd A.; Porter, Dale W.; Bowers, Lauren; Stefaniak, Aleksandr B.; Knepp, Alycia K.; Derk, Raymond; Wolfarth, Michael; et al.
With advances in nanotechnology, engineered nanomaterial applications are a rapidly growing sector of the economy. Some nanomaterials can reach the brain through nose-to-brain transport. This transport creates concern for potential neurotoxicity of insoluble nanomaterials and a need for toxicity screening tests that detect nose-to-brain transport. Such tests can involve intranasal instillation of aqueous suspensions of nanomaterials in dispersion media that limit particle agglomeration. Unfortunately, protein and some elements in existing dispersion media are suboptimal for potential nose-to-brain transport of nanomaterials because olfactory transport has size- and ion-composition requirements. Therefore, we designed a protein-free dispersion media containing phospholipids and amino acids in an isotonic balanced electrolyte solution, a solution for nasal and olfactory transport (SNOT). SNOT disperses hexagonal boron nitride nanomaterials with a peak particle diameter below 100 nm. In addition, multiwalled carbon nanotubes (MWCNTs) in an established dispersion medium, when diluted with SNOT, maintain dispersion with reduced albumin concentration. Using stereomicroscopy and microscopic examination of plastic sections, dextran dyes dispersed in SNOT are demonstrated in the neuroepithelium of the nose and olfactory bulb of B6;129P2- Omp tm3Mom / MomJ mice after intranasal instillation in SNOT. These findings support the potential for SNOT to disperse nanomaterials in a manner permitting nose-to-brain transport for neurotoxicity studies.